Ballistic performance of a composite armor reinforced by alumina balls with various matrix materials: A numerical study - Agustinus Andrie Prasetyo; Aditya Praba Wijaya; Desi Gustiani; Akida Mulyaningtyas; Tri Widodo Besar Riyadi (Universitas Muhammadiyah Magelang, 2025)
This study observed the ballistic performance of the composite armor reinforced by an alumina ball with various matrix materials. The investigation was conducted numerically to establish an effective design of the composite armor for protection against a 7.62 mm bullet impacting at 800 m/s speed. Al 5083, Ti-6Al-4V, Weldox 700E, and Q235 steel, along with ceramic balls acting as reinforcement, make up the composite. The simulation was set in a 3D model and performed using Abaqus finite element software. The outputs of the simulation present the residual velocity, the depth of penetration, the optimized weight-to-penetration depth ratio, and the deformation pattern. The results indicated that the composite armor with ceramic ball reinforcement produced the optimum design using a matrix of Ti-6Al-4V. The matrix with a higher Young modulus has a higher velocity decrease. The matrix with a higher plastic equivalent strength has a higher resistance to the projectile deformation, marked by mushrooming during its penetration. On the contrary, the matrix with a lower plastic equivalent strength forms a ductile hole. This work guides to determination of the optimal design of composite armor containing ceramic balls as reinforcement, considering the different matrix materials.